Composite oxide carrier catalyst as well as preparation method and application thereof
By using a method of combining ZrO2 and Al2O3 with support and doping active metals, the problem of poor catalytic cracking polyethylene in the prior art is solved, and high catalytic efficiency and liquid hydrocarbon yields are improved, which has important applications Value is in the field of plastic recycling.
Patent Information
- Application Number
- CN202411622338.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The prior art has not yet explored the effect of catalysts with ZrO2-Al2O3 as support in catalytic cracking of plastics such as polyethylene, making it difficult to achieve high catalytic efficiency and liquid hydrocarbon yields.
ZrO2 and Al2O3 are used as the support for the catalyst, and the oxide ZrO2 is introduced to improve the mechanical strength and thermal stability of the support. By doping active metals such as Ba, the product distribution of C-C bond fracture and hydrogen adsorption is optimized.
It achieves high catalytic efficiency and high selectivity for liquid hydrocarbon products during polyethylene cracking. The catalytic efficiency exceeds 40%, and the yield of liquid hydrocarbons (C5-C21) exceeds 20%, with excellent thermal stability and resistance to carbon deposits. ability.
Smart Images

Figure CN119488893A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material cracking and catalysts, and in particular to a composite oxide carrier catalyst and a preparation method and application thereof. Background Art
[0002] Plastics are widely used in various industries around the world due to their excellent physical and chemical properties, such as light weight, corrosion resistance, and good insulation. However, the treatment of plastic waste has become a global problem. Most plastics are difficult to degrade in the natural environment. Long-term landfill or incineration not only occupies a large amount of land resources, but also causes serious pollution to the environment. Therefore, finding an effective method for the treatment of plastic waste has become the focus of current research.
[0003] Catalytic pyrolysis technology has broad application prospects as a way to treat plastic waste. This technology converts waste plastics into liquid fuels, gases and solid carbon through a chemical recycling process, providing high value-added opportunities for the reuse of waste plastics. Compared with traditional mechanical treatment methods, catalytic pyrolysis can more efficiently achieve material or energy recovery, reduce environmental burden, and produce by-products with commercial value.
[0004] SiO2-Al2O3 is a traditional carrier of active metals in catalytic reactions. Compared with it, the new ZrO2-Al2O3 carrier shows stronger thermal stability and has better acidity control ability. In addition, the introduction of ZrO2 also improves the mechanical strength and carbon deposition resistance of the carrier, effectively extending the service life of the catalyst. Its high specific surface area and good pore structure further enhance its stability and catalytic efficiency under high temperature conditions. However, the existing technology has not yet explored the effect of catalysts with ZrO2-Al2O3 as carriers on catalytic cracking of plastics such as polyethylene.
[0005] Therefore, developing a composite oxide supported catalyst with good selectivity, high catalytic efficiency and high yield of liquid alkanes for catalytic cracking of polyethylene plastics can obtain high value-added cracking products, which has important application value in the fields of polymer material cracking and recycling of waste plastics. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a composite oxide carrier catalyst and its preparation method and application. The composite oxide carrier catalyst provided by the present invention exhibits high catalytic efficiency and high selectivity for liquid hydrocarbon products in the polyethylene cracking process, and has high application value in the recycling of polyethylene plastics.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In the first aspect, the present invention provides a composite oxide supported catalyst, comprising a carrier and an active metal, wherein the components of the carrier include ZrO2 and Al2O3, and the mass ratio of ZrO2 and Al2O3 is (0.5-5):1; the active metal is at least one of Ba, Pt, Cu, Zn, Co, and Ni, and the mass of the active metal is 0.5-10% of the mass of the composite oxide supported catalyst.
[0009] The present invention uses a combination of ZrO2 and Al2O3 as a catalyst carrier. By introducing the oxide ZrO2, the mechanical strength and thermal stability of the carrier can be significantly improved compared to the traditional carrier, so that the catalyst can maintain the integrity and dispersion of the active site for a long time under high temperature reaction conditions, avoiding the agglomeration or loss of active metals under high temperature conditions; and the doping of active metals promotes CC bond rupture and hydrogen adsorption, improves the yield of light hydrocarbons and liquid fuels, and regulates the acid-base sites, thereby optimizing the product distribution of the cracking reaction and reducing coke generation. The synergistic effect of the active metal in the catalyst of the present invention and the ZrO2-Al2O3 carrier can provide suitable active sites, so that the polyethylene molecular chain undergoes an effective cracking reaction on the catalyst surface, especially in the hydrocracking reaction, to improve the yield of light hydrocarbons.
[0010] The composite oxide carrier catalyst provided by the present invention exhibits significant advantages in the catalytic cracking reaction of polyethylene. The reasonable mass ratio of ZrO2 and Al2O3 enables the carrier to have a distribution of strong acid sites, which helps to improve the efficiency of CC bond cleavage during polyethylene cracking, and significantly improves the reaction activity and product selectivity. When the oxide ratio in the carrier is not suitable, the catalytic efficiency of the catalyst is significantly reduced, and the selectivity for liquid alkanes is reduced.
[0011] The active metal defined in the present invention can adjust the acid strength of the ZrO2-Al2O3 carrier by neutralizing part of the acid sites within the loading range, avoiding excessive cracking of polyethylene caused by excessive acidity and producing too many gas products. Appropriate acidity regulation helps to improve the selectivity of liquid hydrocarbons, making the catalytic cracking reaction more targeted and generating high value-added fuel products. When the loading is too high or too low, the catalytic efficiency of the composite catalyst will be significantly reduced, the gas products will be excessive, and the yield of liquid alkanes will be reduced, which is not conducive to the recovery and reuse of liquid alkanes.
[0012] The composite oxide carrier catalyst of the present invention has a catalytic efficiency of more than 40% and a yield of liquid hydrocarbons (C5-C21) of more than 20% in the polyethylene cracking reaction, showing excellent plastic cracking performance, excellent thermal stability, strong resistance to carbon deposition, and high selectivity for liquid hydrocarbon products, which is more conducive to the generation of high value-added fuel products and has high application value in the recycling and reuse of plastic polyethylene.
[0013] Preferably, the mass ratio of ZrO2 and Al2O3 is (2-5):1.
[0014] Further preferably, the mass ratio of ZrO2 to Al2O3 is 2:1.
[0015] Preferably, the active metal is at least one of Ba and Pt.
[0016] More preferably, the active metal is Ba.
[0017] The present invention selects the most preferred active metal Ba, which interacts with the ZrO2-Al2O3 carrier to provide suitable active sites, so that the polyethylene molecular chains can undergo cracking reactions more effectively on the catalyst surface, especially in hydrogenation cracking reactions, which can further increase the yield of light hydrocarbons (C5-C21 liquid alkanes).
[0018] Preferably, the mass of the active metal is 1-5% of the mass of the composite oxide supported catalyst.
[0019] More preferably, the mass of the active metal is 2.5-5% of the mass of the composite oxide supported catalyst.
[0020] Within the preferred carrier ratio, active metal and active metal dosage range of the present invention, the catalytic efficiency of the composite oxide carrier catalyst in the polyethylene cracking reaction can reach up to 87.8%, and the yield of liquid alkanes (C5-C21) can reach up to 65.3%. The catalytic effect is more excellent and the recovered product has high added value.
[0021] In a second aspect, the present invention provides a method for preparing the composite oxide supported catalyst, comprising the following steps:
[0022] (1) Preparing a carrier: mixing a zirconium oxychloride solution and an aluminum nitrate solution, adding a surfactant, adjusting the pH value to 8-9, stirring until a precipitate is generated, separating the precipitate, washing, drying, and calcining to obtain a carrier powder;
[0023] (2) Loading active metals: The carrier powder is dispersed in water, a soluble active metal salt is added, stirred for adsorption, the solid is separated, washed, dried, and then calcined in an inert atmosphere to obtain the composite oxide carrier catalyst.
[0024] The preparation method of the composite oxide carrier catalyst provided by the present invention first synthesizes the ZrO2-Al2O3 molecular sieve material, i.e. the ZrO2-Al2O3 carrier, by a co-precipitation method, then uniformly loads the active metal on the carrier by an impregnation method, and forms a composite catalyst with good acid-base control ability by high-temperature calcination in an inert atmosphere.
[0025] Preferably, the inert atmosphere is an argon atmosphere.
[0026] Preferably, the surfactant is at least one of cetyltrimethylammonium bromide, polyvinyl pyrrolidone, a triblock copolymer, polyethylene glycol, and sodium dodecyl sulfate.
[0027] Preferably, the calcination temperature is 400-800° C. and the calcination time is 4-8 hours.
[0028] More preferably, the calcination temperature is 550° C. and the calcination time is 4 hours.
[0029] In a third aspect, the present invention provides the use of the above-mentioned composite oxide supported catalyst in polyethylene cracking reaction.
[0030] Preferably, the application comprises the following steps: mixing the composite oxide supported catalyst with polyethylene, and heating the mixture to 300-500° C. in a hydrogen atmosphere for reaction.
[0031] Preferably, the mass ratio of the composite oxide supported catalyst to the polyethylene is 1:(8-12).
[0032] Preferably, in the hydrogen atmosphere, the flow rate of hydrogen is 25-100 mL / min; the heating is to increase the temperature from room temperature to 300-500° C. at a rate of 10° C. / min, and the reaction time is 3-5 hours.
[0033] More preferably, the reaction temperature is 350-400°C.
[0034] In the hydrocracking reaction of polyethylene, the combined effect of the ZrO2-Al2O3 carrier and the active metal in the composite oxide carrier catalyst of the present invention significantly enhances the activity and selectivity of the catalyst, especially at a relatively low temperature of 350-400°C, and can efficiently catalyze the cracking of polyethylene to generate liquid hydrocarbons with high added value.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention provides a composite oxide carrier catalyst, which exhibits strong thermal stability and has more excellent acidity regulation ability by optimizing the ZrO2-Al2O3 carrier and ratio, and the type and loading amount of active metals; the introduced ZrO2 can improve the mechanical strength and carbon deposition resistance of the carrier and extend the service life of the catalyst; its high specific surface area and good pore structure further enhance its stability and catalytic efficiency under high temperature conditions, and exhibits very superior selectivity and reaction efficiency in the reaction of catalytic polyethylene cracking, significantly improving the yield of light hydrocarbons (C5-C21 liquid alkanes), and is more conducive to the production of high value-added fuel products, and has high application value in the recycling and reuse of plastic polyethylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is the XRD pattern of the composite oxide supported catalyst of Example 1-3;
[0038] Figure 2 is a SEM image of the composite oxide supported catalyst of Example 2;
[0039] Figure 3 This is a graph showing the catalytic polyethylene cracking reaction performance of the composite oxide supported catalyst of Example 2 at different reaction temperatures;
[0040] Figure 4 The performance diagram of the polyethylene cracking reaction catalyzed by different active metals in the composite oxide supported catalyst of the embodiment;
[0041] Figure 5 The performance diagram of catalytic polyethylene cracking reaction under different active metal loading amounts in the composite oxide supported catalyst of the embodiment;
[0042] Figure 6 The performance diagram of catalytic polyethylene cracking reaction under different ZrO2-Al2O3 ratios in the composite oxide supported catalyst of the embodiment and the comparative example;
[0043] Figure 7 This is a graph showing the performance of polyethylene cracking reaction catalyzed by a composite oxide supported catalyst with a conventional support as a comparative example. DETAILED DESCRIPTION
[0044] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific examples. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0045] Example 1
[0046] An embodiment of the composite oxide supported catalyst of the present invention, the composite oxide supported catalyst described in this embodiment is a composite catalyst of Ba loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 2:1.
[0047] The preparation method of the composite oxide supported catalyst described in this embodiment is:
[0048] (1) Preparation of carrier:
[0049] Dissolve zirconium oxychloride (ZrOCl2·8H2O) and aluminum nitrate (Al(NO3)3·9H2O) in deionized water to prepare 0.1 M zirconium oxychloride and aluminum nitrate solutions, respectively;
[0050] 10.8 ml of 0.1 M zirconium oxychloride solution and 13.1 ml of 0.1 M aluminum nitrate solution were measured respectively, mixed and stirred evenly, 50 mg of PEG was added to the mixed solution, and 1 M ammonia solution was slowly added dropwise under stirring, the pH value was adjusted to 8-9, and then stirring was continued at room temperature for 2 hours to promote precipitation;
[0051] The obtained precipitate was separated by suction filtration, washed with deionized water several times until the filtrate was close to neutral, the wet precipitate was dried at 80°C for 12 hours, ground into powder, and then calcined at 550°C for 4 hours to obtain ZrO2-Al2O3 carrier powder.
[0052] (2) Loading active metals:
[0053] Weigh 1 g of the ZrO2-Al2O3 carrier powder prepared in step (1), disperse it in 200 ml of deionized water, and slowly drop 3.84 ml of 0.1 M BaCl2 solution into the ZrO2-Al2O3 suspension while stirring.
[0054] Stirring was continued for 12 hours to ensure that Ba 2+ The obtained solid is evenly distributed and adsorbed onto the surface of ZrO2-Al2O3, and the obtained solid is separated by suction filtration, washed with deionized water until the filtrate is colorless, and then dried at 80°C for 12 hours, and the obtained solid is ground into powder, and finally reduced at 400°C in an argon atmosphere for 4 hours to obtain the composite oxide carrier catalyst.
[0055] The XRD pattern of the composite oxide supported catalyst 5% Ba / ZrO2-Al2O3 prepared in the present invention is as follows: Figure 1 shown.
[0056] Example 2
[0057] An embodiment of the composite oxide supported catalyst of the present invention, the composite oxide supported catalyst described in this embodiment is a composite catalyst of Ba loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 2:1.
[0058] The method for preparing the composite oxide supported catalyst described in this example is different from that in Example 1 in that the amount of BaCl2 solution added in step (2) is 1.87 ml.
[0059] The XRD pattern of the composite oxide supported catalyst 2.5% Ba / ZrO2-Al2O3 prepared by the present invention is as follows: Figure 1 The scanning electron microscope observation is shown in Figure 2 .
[0060] Example 3
[0061] An embodiment of the composite oxide supported catalyst of the present invention, the composite oxide supported catalyst described in this embodiment is a composite catalyst of Ba loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 1.25% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 2:1.
[0062] The method for preparing the composite oxide supported catalyst described in this example is different from that in Example 1 in that the amount of BaCl2 solution added in step (2) is 0.92 ml.
[0063] The XRD pattern of the composite oxide supported catalyst 1.25% Ba / ZrO2-Al2O3 prepared by the present invention is as follows: Figure 1 shown.
[0064] Example 4
[0065] An embodiment of the composite oxide supported catalyst of the present invention, the composite oxide supported catalyst described in this embodiment is a composite catalyst of Ba loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 5:1.
[0066] The method for preparing the composite oxide supported catalyst described in this example is different from that in Example 2 in that the amount of zirconium oxychloride solution used in step (1) is 27 ml.
[0067] Example 5
[0068] An embodiment of the composite oxide supported catalyst of the present invention, the composite oxide supported catalyst described in this embodiment is a composite catalyst of Ba loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 0.5:1.
[0069] The method for preparing the composite oxide supported catalyst described in this example is different from that in Example 2 in that the amount of zirconium oxychloride solution used in step (1) is 2.7 ml.
[0070] Example 6
[0071] An embodiment of the composite oxide supported catalyst of the present invention, the composite oxide supported catalyst described in this embodiment is a composite catalyst of Pt loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Pt is 2.5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 2:1.
[0072] The method for preparing the composite oxide supported catalyst described in this example is different from that in Example 2 in that the barium chloride solution used is replaced with 1.32 ml of a PtCl4 solution of the same concentration.
[0073] Example 7
[0074] An embodiment of the composite oxide supported catalyst of the present invention, the composite oxide supported catalyst described in this embodiment is a composite catalyst of Zn loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Zn is 2.5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 2:1.
[0075] The method for preparing the composite oxide supported catalyst described in this example is different from that in Example 2 in that the barium chloride solution used is replaced with 3.95 ml of a ZnCl2 solution of the same concentration.
[0076] Comparative Example 1
[0077] A composite catalyst of Ba loaded on a SiO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of SiO2 to Al2O3 in the carrier is 5:1. The preparation method thereof is different from that of Example 2 only in that the zirconium oxychloride solution used in step (1) is replaced by 55.46 ml of sodium silicate (Na2SiO3) solution of the same concentration.
[0078] Comparative Example 2
[0079] A composite catalyst of Ba loaded on a SiO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of SiO2 to Al2O3 in the carrier is 2:1. The preparation method thereof is different from that of Example 2 only in that the zirconium oxychloride solution used in step (1) is replaced by 22.18 ml of sodium silicate (Na2SiO3) solution of the same concentration.
[0080] Comparative Example 3
[0081] A composite catalyst of Ba loaded on a SiO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of SiO2 to Al2O3 in the carrier is 0.5:1. The preparation method thereof is different from that of Example 2 only in that the zirconium oxychloride solution used in step (1) is replaced by 5.55 ml of sodium silicate (Na2SiO3) solution of the same concentration.
[0082] Comparative Example 4
[0083] A composite catalyst of Ba loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 10:1. The preparation method thereof is different from that of Example 2 in that the amount of zirconium oxychloride solution used in step (1) is 54 ml.
[0084] Comparative Example 5
[0085] A composite catalyst of Ba loaded on a ZrO2-Al2O3 carrier, wherein the loading amount of active metal Ba is 2.5% of the total mass of the catalyst, and the mass ratio of ZrO2 to Al2O3 in the carrier is 0.25:1. The preparation method thereof is different from that of Example 2 in that the amount of zirconium oxychloride solution used in step (1) is 1.35 ml.
[0086] Effect Example 1
[0087] In order to explore the reaction temperature of the composite oxide supported catalyst provided by the present invention in the application of catalytic cracking of polyethylene, the following catalytic experiment was carried out on the composite oxide supported catalyst in Example 2:
[0088] Weigh 0.5g of the catalyst in Example 2 and mix it evenly with 5g of polyethylene, add it to the reaction tank, place the reaction tank in a fixed bed reactor, first pass argon gas for 1h, then pass hydrogen gas for 1h, the flow rate is 100ml / min. After the purging is completed, the temperature is raised to 300℃, 350℃, and 400℃ at a rate of 10℃ / min, and the reaction time is 4 hours. After the reaction is completed, the gas, liquid and solid residues in the reaction product are collected and analyzed to determine the cracking efficiency and product distribution of the catalyst. The results are shown in Table 1 and the comparative analysis of catalytic performance is shown in Figure 1. Figure 3 .
[0089] From Table 1 and Figure 3 It can be seen that: when the composite oxide supported catalyst of the present invention is used and the temperature is raised to 350°C for the cracking reaction of polyethylene, the catalytic efficiency is the highest, the yield of C5-C21 liquid alkanes is high, and the comprehensive catalytic effect is the best. Lowering or increasing the temperature will lead to a decrease in the catalytic efficiency, and the yield of liquid alkanes may be significantly reduced, while the product yield increases.
[0090] Table 1 Performance results of polyethylene cracking reaction catalyzed by the catalyst of Example 2 at different reaction temperatures
[0091] Reaction temperature 300℃ 350℃ 400℃ Catalytic efficiency 65.30% 87.80% 73.60% C5-C21 liquid alkane yield 33.80% 65.30% 38.90%
[0092] Effect Example 2
[0093] In order to further explore the specific application effect of the composite oxide supported catalyst provided by the present invention in catalytic cracking of polyethylene, the following catalytic experiments were carried out on the catalysts in the examples and comparative examples:
[0094] Weigh 0.5g of the catalyst in each embodiment and comparative example and mix them evenly with 5g of polyethylene, add them to the reaction tank, place the reaction tank in a fixed bed reactor, first pass argon gas for 1h and then pass hydrogen for 1h, the flow rate is 100ml / min. After the purging is completed, the temperature is raised to 350℃ at a rate of 10℃ / min, and the reaction time is 4 hours. After the reaction is completed, the gas, liquid and solid residue in the reaction product are collected and analyzed to determine the cracking efficiency and product distribution of the catalyst. The results are shown in Table 2 and the comparative analysis of catalytic performance is shown in Figure 2. Figure 4-7 , we can know that:
[0095] (1) Comparative Table 2, in Examples 1-7, the composite oxide carrier catalysts with specific ZrO2-Al2O3 carriers and carrier ratios provided by the present invention have better catalytic cracking efficiency for polyethylene, and are generally superior to the catalysts in the comparative examples whose carriers are SiO2-Al2O3 or whose carriers have an inappropriate ZrO2-Al2O3 ratio; among them, under the selection of active metals and carrier ratios of the composite oxide carrier catalysts in Example 2, the catalytic effect on polyethylene is optimal, the catalytic efficiency can reach 87.80%, and the yield of liquid alkanes (C5-C21) can be as high as 65.30%, which can achieve efficient catalytic cracking of polyethylene and a high yield of high value-added fuel products;
[0096] (2) By Figure 4 The catalytic performance comparison shows that different active metal selections affect the catalytic cracking effect of the composite oxide supported catalyst of the present invention on polyethylene. When other conditions remain unchanged, the catalytic efficiency and the yield of C5-C21 liquid alkanes are both Ba>Pt>Zn. Figure 5 The comparison of the catalytic performance in the results shows that different active metal loadings also have a certain influence on the catalytic effect of the composite oxide carrier catalyst of the present invention. The optimal loading of the active metal Ba is 2.5%. A loading higher or lower than this loading will reduce the catalytic efficiency and significantly reduce the yield of C5-C21 liquid alkanes.
[0097] (3) By Figure 6 It can be seen from the comparison of the catalytic performance that when the mass ratio of ZrO2 and Al2O3 in the carrier is within the specified range of the present invention, the catalytic efficiency can reach more than 55%, the yield of C5-C21 liquid alkanes is more than 35%, and the catalytic cracking effect is significantly better than that of comparative examples 3 and 4 with inappropriate ratios; Figure 7 The catalytic performance results show that under the same conditions, when using traditional SiO2-Al2O3 carrier loading, the catalytic effect of different carrier ratios is significantly deteriorated.
[0098] From the above, it can be seen that the present invention adopts a combination of ZrO2 and Al2O3 as a carrier of the catalyst. By introducing the oxide ZrO2, the mechanical strength and thermal stability of the carrier can be significantly improved compared with traditional carriers, so that the catalyst can maintain the integrity and dispersion of the active sites for a long time under high-temperature reaction conditions, avoiding the agglomeration or loss of active metals under high-temperature conditions, and significantly improving the catalytic effect; and the preferred active metal doping promotes CC bond breaking and hydrogen adsorption, improves the yield of light hydrocarbons and liquid fuels, and regulates acidic and alkaline sites, thereby optimizing the product distribution of the cracking reaction, increasing the yield of C5-C21 liquid alkanes, and realizing the recovery and utilization of high-net-value products of polyethylene cracking, which has high practical value.
[0099] Table 2 Performance results of the catalysts in the examples and comparative examples for catalytic polyethylene cracking reactions
[0100]
[0101]
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A composite oxide supported catalyst, characterized in that: It includes a carrier and an active metal, wherein the components of the carrier include ZrO2 and Al2O3, and the mass ratio of ZrO2 and Al2O3 is (0.5-5):1; the active metal is at least one of Ba, Pt, Cu, Zn, Co, and Ni, and the mass of the active metal is 0.5-10% of the mass of the composite oxide carrier catalyst.
2. The composite oxide supported catalyst according to claim 1, characterized in that The mass ratio of ZrO2 and Al2O3 is (2-5):
1.
3. The composite oxide supported catalyst according to claim 1, characterized in that The active metal is at least one of Ba and Pt.
4. The composite oxide supported catalyst according to claim 1, characterized in that The mass of the active metal is 1-5% of the mass of the composite oxide supported catalyst.
5. The method for preparing a composite oxide supported catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparing a carrier: mixing a zirconium oxychloride solution and an aluminum nitrate solution, adding a surfactant, adjusting the pH value to 8-9, stirring until a precipitate is generated, separating the precipitate, washing, drying, and calcining to obtain a carrier powder; (2) Loading active metals: The carrier powder is dispersed in water, a soluble active metal salt is added, stirred for adsorption, the solid is separated, washed, dried, and then calcined in an inert atmosphere to obtain the composite oxide carrier catalyst.
6. The method for preparing the composite oxide supported catalyst according to claim 5, characterized in that: The surfactant is at least one of cetyltrimethylammonium bromide, polyvinyl pyrrolidone, triblock copolymer, polyethylene glycol, and sodium dodecyl sulfate.
7. The method for preparing a composite oxide supported catalyst according to claim 5, characterized in that: The calcination temperature is 400-800° C. and the calcination time is 4-8 hours.
8. Use of the composite oxide supported catalyst according to any one of claims 1 to 4 in polyethylene cracking reaction.
9. Use of the composite oxide supported catalyst in polyethylene cracking reaction as claimed in claim 8, characterized in that: The application The method comprises the following steps: mixing the composite oxide carrier catalyst with polyethylene, and heating the mixture to 300-500° C. in a hydrogen atmosphere for reaction.
10. Use of the composite oxide supported catalyst according to claim 9 in polyethylene cracking reaction, characterized in that: The mass ratio of the composite oxide carrier catalyst to the polyethylene is 1:(8-12).
Citation Information
Patent Citations
Alumina-zirconia composite carrier and preparation method thereof
CN102247896A
Catalyst for producing fuel oil through catalytic cracking of waste plastic and preparation method of catalyst
CN109158100A
Method for directly preparing aviation gasoline and aviation kerosene from polyolefin waste plastics
CN113502174A
Process for treating plastic pyrolysis oil comprising one-step hydrocracking
CN116209737A
Cracking-gas modifying catalyst for oil-production by waste plastic and preparation method thereof
CN1438295A